Evaluation of Hazardous and Toxic Solid Waste Management in Cancer Patient Care Rooms at the Cancer Center Building, RSUP Fatmawati Jakarta, 2024 - Alfarel, Muhammad Adny; Sulistiyorini, Desy; Rindu, Rindu (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Fatmawati Central General Hospital (RSUP Fatmawati) is a Type A hospital based on education and research for health workers in providing health services that will produce hazardous solid waste that can interfere with health if not managed properly and correctly. The purpose of this study is to determine how the process of implementing hazardous solid waste management in cancer patient care rooms is carried out. Method: This study is observational in nature, using a qualitative descriptive research design with in-depth interviews, observations, and document reviews. The informants in this study include the environmental health department, solid waste supervisors, the Cancer Center building manager, the cleaning service manager, and six cleaning staff members. Results: The study concluded that the management of infectious medical waste and non-infectious medical waste in the cancer patient care unit of the Cancer Center Building at RSUP Fatmawati, from the sorting stage, containment, transportation, temporary storage at the TPS, and processing in collaboration with the second party, as well as the facilities and infrastructure used in the management of hazardous solid waste (B3), are in accordance with applicable regulations. Conclusion: The management of solid B3 waste at the Cancer Center Building of RSUP Fatmawati Hospital is in accordance with regulations and standard operating procedures for solid B3 waste management, specifically infectious medical waste and non-infectious medical waste in the cancer patient care unit, which are in compliance with applicable regulations.